Learning Innovations in Islamic Religious Education in the Context of Increasing the Effectiveness of Learning - Susanti, Desi (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
To create effective Islamic Religious Education learning in the classroom, teachers need to innovate learning, so that learning in the classroom is not monotonous and not boring, so that learning achievement targets are not met. Innovations carried out by teachers can be carried out by using various methods, using media, evaluation and so on. Considering the importance of innovation in the Islamic Religious Education learning system, the problem formulation in this research is; 1) What are the innovations in learning Islamic Religious Education at PKBM (Learning Activity Center Of Public) Literasi Bangsa Kejayan Pujer Bondowoso? 2) What are the results of the implementation of Islamic Religious Education learning innovations at PKBM Literasi Bangsa Kejayan Pujer Bondowoso?This research uses a qualitative approach with a